Autosomal Recessive Cutis Laxa 1C Mutations Disrupt the Structure and Interactions of Latent TGFβ Binding Protein-4 - Alanazi, Yasmene F.; Lockhart-Cairns, Michael P.; Cain, Stuart A.; Jowitt, Thomas A.; Weiss, Anthony S.; Baldock, Clair (Frontiers in Genetics, 2021)
Latent TGFβ binding protein 4 (LTBP4) is a multi-domain glycoprotein, essential for regulating the extracellular bioavailability of TGFbeta and assembly of elastic fibre proteins, fibrillin-1 and tropoelastin. LTBP4 mutations are linked to autosomal recessive cutis laxa type 1C (ARCL1C), a rare congenital disease characterized by high mortality and severely disrupted connective tissues. Despite the importance of LTBP4, the structure and molecular consequences of disease mutations are unknown. Therefore, we analysed the structural and functional consequences of three ARCL1C-causing point mutations which effect highly conserved cysteine residues. Our structural and biophysical data show that the LTBP4 N- and C-terminal regions are monomeric in solution and adopt extended conformations with the mutations resulting in subtle changes to their conformation. Similar to LTBP1, the N-terminal region is relatively inflexible whereas the C-terminal region is flexible. Interaction studies show that one C-terminal mutation, slightly decreases binding to fibrillin-1. We also found that the LTBP4 C-terminal region directly interacts with tropoelastin which is perturbed by both C-terminal ARCL1C mutations. Whereas, an N-terminal mutation increased binding to fibulin-4 but did not affect the interaction with heparan sulphate. Our results suggest that LTBP4 mutations contribute to ARCL1C by disrupting the structure and interactions of LTBP4 which are essential for elastogenesis in a range of mammalian connective tissues.